Rhétorique et autorité historique : la corruption de la Pythie chez Hérodote - Dainville, Julie (Rivista Italiana di Filosofia del Linguaggio)
The fact that the Pythia was a first plan character in Herodotus’ Histories and the respect that the historian devoted to her is no longer to be demonstrated. The most famous illustration of this high consideration is probably to be found in the narrative of Croesus’s devotion towards Apollo and his oracle at Delphi, but several passages confirm this particular status. Herodotus also reports two corruption cases involving the Pythia but, surprisingly, this does not compromise his trust and the authority of the sanctuary. The aim of this article is to show that the paradox is only apparent. In order to do so, I will begin by a rhetorical and linguistic analysis of the mechanisms (mainly from lexical and syntactic points of view) used by the historian to preserve the Pythia as a function. Then I will compare the two corruption cases involving the Pythia found in the Histories to highlight the different effects produced by Herodotus’ linguistic choices.